ECO TOURISM DEVELOPMENT STRATEGY IN SEMARANG CITY: Case of Mangrove Tugurejo Ecotourism - Yuswinarto, Rahardyan Haris; Aminata, Jaka; Susilowati, Indah (LP2M Institut Teknologi dan Bisnis Asia Malang, 2022)
This study aims to design an ecotourism development strategy and calculate its economic value. The research method used is a